Pendekatan Kooperatif Think Pair Share (TPS) dan Investigasi Kelompok dalam Pembelajaran PAI: Inovasi Pedagogis dalam Penguatan Nilai Islami dan Kemandirian Belajar - Rifqiya Zahara; Syach Dilla Bi Rizqi Yahya; M. Yunus Abu Bakar (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the application of Think-Pair-Share (TPS) and Group Investigation (GI) cooperative learning strategies as pedagogical innovations in strengthening Islamic values and student learning independence in Islamic Religious Education (IRE) subjects. This study uses a library research method by examining various relevant scientific sources, including cooperative learning theory, the concept of independent learning, and Islamic educational values. The results of the study show that the integration of TPS and GI strategies can create an active, participatory, collaborative, and reflective learning process. Through paired discussions and investigative group work, students are trained to think critically, be responsible, and be able to work together harmoniously. In addition to improving academic understanding, the application of these two strategies also contributes to instilling Islamic values such as ukhuwah (brotherhood), amanah (trustworthiness), and mutual respect. Thus, this learning innovation is not only oriented towards cognitive aspects, but also towards character building and spirituality of students. The findings of this study are expected to be a reference for PAI teachers in developing effective, contextual, and Islamic character learning strategies.